Paritas dan Pemenuhan Gizi Seimbang Terhadap Kejadian KEK Pada Ibu Hamil - Yanti, Nuri; Qomari, Selvia Nurul (NHM PRESS, 2024)
Chronic Energy Deficiency is a nutritional disorder that is still experienced by many pregnant women. The purpose of the study is to provide benefits to pregnant women, especially for pregnant women who are still experiencing CED so that they can maintain their balanced nutrition and can reduce the incidence of CED in the next years. The research design used was analytic with a cross sectional approach with samples of 27 pregnant women who carried out Integrated ANC at the their Tragah Health Center Bangkalan. The Independent variable was parity and fulfillment of balanced nutrition, while the dependent variable was CED. The result of this research shows us that majority of pregnant women were multigravida and those who well- fulfilled and sufficient balanced nutrition, did not experience CED. So it can be concluded that there was no relationship between parity and balanced nutrition fulfilment with the incidence of CED in pregnant women (ρ-value 0.689). It is necessary for the health workers to provide supplementary food, increase services in the field of counseling, and provide education related to balanced and nutritious food, especially for pregnant women to prevent CED.